Effect of running high-intensity interval training type of recovery on muscle injury and oxidative stress markers - Danielli Mello; Thiago Dias Sales; Stefano Amaral Flores; Mario Lucio Souza Junior; Filipe Alves Farias; Marcio Antonio de Barros Sena; Marcos Dias Pereira; Guilherme Rosa Abreu; Rodrigo Gomes de Souza Vale (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2023)
Introduction: High Intensity Interval Training (HIIT) is understood as vigorous activity, with different intensities, interspersed with periods passive or active recovery, which induces an acute physiological response. Two running HIITs were analyzed, and biochemical markers of muscle damage (MD) and oxidative stress (OS) were measured. Materials and Methods: 15 soldiers were submitted to anthropometric and VO2 max assessments. Subsequently, they performed treadmill running HIITs: (a) moderate to strong intensity and active recovery (HIIT AR) and, (b) moderate to strong intensity with passive recovery (HIIT PR). Venous blood samples were collected pre and post-tests for analysis of MD (lactate, creatine kinase - CK and lactate dehydrogenase - LDH), and OS (lipid peroxidation- LP, carbonyl protein - PC, total antioxidant activity -TAA and total sulfhydryl groups - TSG). Results: Comparing MD at baseline x HIIT PR, it was observed an increase in CK, LDH and lactate. At baseline x HIIT AR, a significant increase in CK, LDH and lactate. Comparing HIIT RP x HIIT AR, only lactate was significantly affected by HIITs. Comparing OS at baseline x HIIT PR, there was a significant increase in LP and PC. Baseline x HIIT AR, there was a reduction only at TSG, and comparing HIIT PR x HIIT AR, there was a reduction in LP/VO2, TSG and PC. Conclusion: Both protocols increased blood levels of MD, but comparing HIIT PR and HIIT AR, lactate and OS were higher at HIIT PR. It is noteworthy that HIIT AR is more effective in removing lactate and modulating redox metabolism